The Effect Of Capital Structure, Cash Holding, And Firm Size On Firm Value With Corporate Governance As A Moderating Variable (Empirical Study On Mining Companies In 2015 - 2019) - Yohanes Agung Nugroho; Dwi Asih Surjandari (The Accounting Journal of Binaniaga, 2022)
ABSTRACT.This present study aimed to examine the effect of capital structure, cash holding, and firm size on firm value with corporate governance as the moderator, empirical study on mining companies in 2015-2019. The population in this study were mining companies. The period used was 2015-2019. The sample obtained by purposive sampling method was of 45 data, and was done by using the eViews 8.0 statistical test. The statistical test results revealed that capital structure did not have significant effect on firm value, cash holding had a significant effect on firm value, firm size did not have significant effect on firm value, capital structure moderated by corporate governance did not have significant effect on firm value and cash holding moderated by Corporate governance had a significant effect on firm value.